PANCASILA SEBAGAI DASAR FALSAFAH PAJAK DI INDONESIA - Thomas Abbon (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract It has become a national consensus that the Pancasila is the basic philosophy of the state and nation of Indonesia, which underlies all actions and deeds in the life of the state and society. Through TAP MPRS No. XX / MPRS / 1966 it has been established that Pancasila is the source of all sources of law in Indonesia. The consequence is that any existing laws and regulations must be based and must not con ict with Pancasila, including taxation. Keywords: national consensus; Pancasila; tax; laws and regulations.